2021
DOI: 10.3390/ijerph18030909
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Insulin Resistance and the Associated Risk Factors in a Sample of 14–18-Year-Old Slovak Adolescents

Abstract: The prevalence of cardiometabolic risk factors has increased in Slovakian adolescents as a result of serious lifestyle changes. This cross-sectional study aimed to assess the prevalence of insulin resistance (IR) and the associations with cardiometabolic and selected lifestyle risk factors in a sample of Slovak adolescents. In total, 2629 adolescents (45.8% males) aged between 14 and 18 years were examined in the study. Anthropometric parameters, blood pressure (BP), and resting heart rate were measured; fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In contrast, the risk of IR increased significantly between patients in the first and third tertiles of BMI (>24.2 kg/m 2 ). This shows IR occurs more significantly who demonstrated that the prevalence of IR in adolescents was strongly associated with overweight and obesity [27]. Similarly, Elrayess et al reported a linear relationship between IR and BMI in a cross-sectional study on 150 young healthy females from Qatar [28].…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, the risk of IR increased significantly between patients in the first and third tertiles of BMI (>24.2 kg/m 2 ). This shows IR occurs more significantly who demonstrated that the prevalence of IR in adolescents was strongly associated with overweight and obesity [27]. Similarly, Elrayess et al reported a linear relationship between IR and BMI in a cross-sectional study on 150 young healthy females from Qatar [28].…”
Section: Discussionmentioning
confidence: 92%
“…The 15 primary studies included in our systematic review were all cross-sectional studies [ 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and no new articles were included after the snowballing process.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included reported pediatric MetS data regarding European countries; specifically, 34% ( n = 5) were conducted in Spain [ 19 , 26 , 27 , 28 , 29 ], 13% ( n = 2) in Romania [ 21 , 22 ], 13% ( n = 2) in Italy [ 13 , 24 ], 13% ( n = 2) in Poland [ 17 , 18 ], 13% ( n = 2) in Slovakia [ 23 , 25 ], 1 (7%) in Lithuania [ 18 ], and 1 (7%) in the Czech Republic [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies revealed that cardiovascular mortality and morbidity raise with BMI 18 . Although BMI is useful for determining obesity, it is not, precise enough to detect early fat gathering and early cardiovascular hazard 19 . Although, the most important aim of protective pediatrics is to check children with higher cardiovascular risk as soon as possible 18 .…”
Section: Discussionmentioning
confidence: 99%